3.9G Radio Reception with SC-FDMA Waveforms Under I/Q Imbalance - Anttila, Lauri; Valkama, Mikko; Renfors, Markku (2007 IEEE International Symposium on Circuits and Systems (ISCAS), 2007)
The so-called single-carrier FDMA (SC-FDMA) waveform class, also known as DFT-spread OFDM, is a special form of multi-carrier modulation, and has received a lot of interest in 3.9G system context recently. This paper addresses the radio implementation and RF impairment issues related to the reception of SC-FDMA waveforms. The main emphasis is on the so-called I/Q imbalance problem which in general results in imperfect attenuation of the mirror-frequencies. Here, the role of mirror-frequencies and mirror-frequency interference is addressed in detail from the SC-FDMA signals point of view, covering both the localized and distributed transmission modes. Furthermore, under perfect I/Q balance, it is shown that SCFDMA signals satisfy certain circularity conditions related to the second-order statistics of complex random signals. This circularity, on the other hand, is lost due to I/Q imbalance which can then be used as a basis for developing efficient digital signal processing (DSP) -based algorithms to compensate for the I/Q imbalance effects. Comprehensive system simulations are carried out in both the localized and distributed spectral deployment cases, with and without digital compensation, to illustrate the relative effects of I/Q imbalances and the compensation stage on the overall system performance.